Redescription of Vertigo (Vertigo) nitidula (Mousson, 1876) (Gastropoda: Vertiginidae) from the Caucasus region - Walther, Frank; Kijashko, Pavel V.; Hausdorf, Bernhard (Zootaxa, 2014)
A revision of material of a minute land snail species from the Caucasus region usually named Vertigo (Vertigo) sieversi (Boettger, 1879) (Pilsbry 1919; Schileyko 1984; Sysoev & Schileyko 2005; Egorov 2008; Sysoev & Schileyko 2009), including types of all described varieties revealed that adjustments of the delimitation and the nomenclature of this insufficiently known taxon are necessary. We reinstate the oldest available name, Vertigo (Vertigo) nitidula (Mousson, 1876), for this species, redescribe it, and discuss its distinction from Vertigo (Vertigo) substriata (Jeffreys, 1833) as well as its geographical range.